Too Lucky to be True - Fairness Views under the Shadow of Cheating - Stefania Bortolotti; Ivan Soraperra; Matthias Sutter; Claudia Zoller (Center for Economic Studies and ifo Institute (CESifo), 2017)
The steady increase in inequality over the past decades has revived a lively debate about what can be considered a fair distribution of income. Public support for the extent of redistribution typically depends on the perceived causes of income inequality, such as differences in effort, luck, or opportunities. We study how fairness views and the extent of redistribution are affected by a hitherto overlooked, but relevant factor: immoral self-serving behavior that can lead to increased inequality. We focus on situations in which the rich have potentially acquired their fortunes by means of cheating. In an experiment, we let third parties redistribute resources between two stakeholders who could earn money either by choosing a safe amount or by engaging in a risky, but potentially more profitable, investment. In one treatment, the outcome of the risky investment is determined by a random move, while in another treatment stakeholders can cheat to obtain the more profitable outcome. Although third parties cannot verify cheating, we find that the mere suspicion of cheating changes fairness views of third parties considerably and leads to a strong polarization. When cheating opportunities are present, the share of subjects redistributing money from rich to poor stakeholders triples and becomes as large as the fraction of libertarians - i.e., participants who never redistribute. Without cheating opportunities, libertarian fairness views dominate, while egalitarian views are much less prevalent. These results indicate that fairness views and attitudes towards redistribution change significantly when people believe that income inequality is the result of cheating by the rich.
Keywords: C91; D63; D81; H26; 330; fairness views; redistribution; unethical behavior; inequality; experiment